RAGAM LAKON PERAN AUDITOR DALAM PEMERIKSAAN BANSOS HIBAH - Anggun Anita Sari; Zaenal Fanani (Universitas Negeri Malang, 2018)
This study aims to describe how the reality of the role of internal auditors of local government in carrying out the task of social assistance and grant audit. The internal auditor of the government is considered merely to waive its obligations. Implementation of social assistance and grants has always been an important notice of BPK in its Opinion of the Local Government Financial Report Indraprasta. Using the methodology of phenomenology, the results of this study found that there is a role implementation stated as a